PERAN KEPALA SEKOLAH DALAM MEMBENTUK BUDAYA ISLAMI DI MA NASYATUL MUTA’ALLIMIN I GAPURA TIMUR, SUMENEP - Edi Susanto; Hosnani Hosnani (re-JIEM (Research Journal of Islamic Education Management), 2018)
A school is where the internalization of religious culture to the students, so that they have a strong fortress in forming a noble character. Application of Islamic culture in an institution not be separated from the role of head of the school where the principal is responsible for the smooth implementation of education and teaching in School. The principal must be resourceful in the lead group and the delegation of duties and authorities. In the administration of activities contains in it the functions of planning, organizing, staffing, and supervision. A successful prinsipal is a participal who understand about any factors which make him be able to lead a school so that facilitate him in determining steps to make the success come true including the success in shaping islamic culture.